Evaluation of natural immunostimulants for growth promotion and protection against Aeromonas hydrophila in juvenile Red hybrid tilapia (Oreochromis sp.) - Hamid, Nur Hidayahanum (2014)
Aeromonas hydrophila is widely known as one of the common bacteria species in freshwater habitats and occasionally been recognized as a fish pathogen. In Malaysia, the use of immunostimulants especially in aquaculture industry has not been studied widely due to the lack of promotion and education especially to fish farmers. Hence, this study was conducted to identify A. hydrophila from disease freshwater fish. The bacteria were also used to perform antimicrobial sensitivity tests. Two types of immunostimulants (Lipopolysaccharide and β-glucan) were used to evaluate the changes in the haematology, non-specific immune response, disease resistance and growth performance of juvenile Red hybrid tilapia (Oreochromis sp.).In the present study, the isolates of A. hydrophila were subjected for Gram’s staining and the identity of the isolates were confirmed by using API 20E® kit in combination with oxidase and catalase tests. The isolates were also inoculates on horse blood and Rimler-Shotts agar. Antimicrobial sensitivity test was also done by using Kirby- Bauer method. Then, pathogenicity of A. hydrophila was expressed as median lethal dose (LD50) and moribund fish were proceed to histopathological examination. After that, the efficacy of lipopolysaccharide (LPS) and β-glucan was studied in juvenile Red hybrid tilapia (Oreochromis sp.) against A. hydrophila. The fish were divided into seven different groups of test including control which consisting of 15 fish pergroup. Each group had two replicates. Different concentration of LPS and β-glucan were used for intraperitoneal injection (i.p.), long-term bath exposure and oral feeding, they were 50 μg/fish, 50 μg/L and 25 mg/kg, respectively. For intraperitoneal injection and long-term bath exposures, LPS and β-glucan were administered to the test fish on day 1, 7 and 14. While for oral feeding, the test fish were fed with commercial pellet added with LPS and β-glucan daily until day 40. On day 7, blood samples were collected from each group to examine the haematological parameters of the test fish. Control and test fish were challenged with LD50 concentration of A. hydrophila by i.p. on day 16 (i.p injection and bath exposures) and on day 41 (oral). Mortality rate and RPS (Relative Percentage Survival) were then calculated. Daily mortality was recorded for a week. From the study, 11 isolates of bacteria were successfully identified by using morphological, biochemical (conventional and commercial kit) and physiological tests. The bacteria isolates were characterized as Gram-negative, motile, catalase positive, oxidase positive,possessed straight rod cell; approximately up to 3 μm in length which appeared in singles and pairs. The isolates showed β-haemolysis on horse blood agar and were able to grow on selective agar (Rimler-Shott agar). All bacteria isolates were found to be sensitive towards streptomycin, kanamycin, chloramphenicol and gentamicin but showed resistant to amoxicillin. In a pathogenicity test run by intraperitoneal injection, the infection caused marked clinical sign of abnormalities such as exophthalmia, lethargy, enlargement of kidney, spleen and liver. Histopathological examinations showed marked congestion and haemorrhages in the spleen, liver and kidney tissues. The median lethal dose (LD50) at 96 hours of the isolate for juvenileRed hybrid tilapia (Oreochromis sp.) was 6.3 x 106 cfu/ml. Administration of LPS and β-glucan by intraperitoneal injection, long-term bath exposure and oral feeding significantly enhanced the RPS. The survivability was higher in fish treated with both compounds, which was significantly high (more than 50%) when compared to control group (less than 50%). The results indicated that oral feeding had the highest survival among the treatment groups followed by i.p injection and bath due to the long duration of feeding exposure. In haematological assay, there were no significant difference between control and treated groups. However, the fish administered with LPS and β-glucan showed significant increased in total leucocytes count (P < 0.05) and also significantly (P < 0.05) improve the growth performance of tested fish compared with the control group. In histopathological examinations, different types of MMC (melano-macrophage centre) were observed in spleen tissues of control and treated groups. The present study revealed that the presence of numerous hemosiderin granules (brownish yellow) was higher in the spleen of control group compared to treated groups. The MMC in the treated group was more enriched in melanin pigment which is dark pigment-containing cells (macrophage).The findings in this study indicates that A. hydrophila infection has become an important health issue in tilapia farms. This study also demonstrates that LPS and β-glucan administration through injection, long-term bath exposures and oral feeding effectively stimulates the non-specific cellular as well as growth performances and offers protection against A. hydrophila infection in juvenile Red hybrid tilapia (Oreochromis sp.). Data from biochemical tests, haematological and histological studies provide valuable and previously unknown information associates with A. hydrophila in cultured juvenile Red hybrid tilapia (Oreochromis sp.). In addition, this study also reveals that LPS and β-glucan could be used as an alternative for prophylaxis against A. hydrophila infection and the important of long term exposure of immunostimulants to obtain maximum protection against bacterial infection.